Analysis of inter- and intrafraction accuracy of a commercial thermoplastic mask system used for image-guided particle radiation therapy - Amelio, Dante; Winter, Marcus; Habermehl, Daniel; Jäkel, Oliver; Debus, Jürgen; Combs, Stephanie (Journal of radiation research, 2013)
The present paper reports and discusses the results concerning both the inter- and intrafraction accuracy achievable combining the immobilization system employed in patients with head-and-neck, brain and skull base tumors with image guidance at our particle therapy center. Moreover, we investigated the influence of intrafraction time on positioning displacements. A total of 41 patients treated between January and July 2011 represented the study population. All the patients were immobilized with a tailored commercial thermoplastic head mask with standard head-neck rest (HeadSTEP®, IT-V). Patient treatment position was verified by two orthogonal kilovoltage images acquired through a ceiling imaging robot (Siemens, Erlangen, Germany). The analysis of the applied daily corrections during the first treatment week before and after treatment delivery allowed the evaluation of the interfraction and intrafraction reproducibility of the thermoplastic mask, respectively. Concerning interfraction reproducibility, translational and rotational systematic errors (Σs) were ≤2.2 mm and 0.9º, respectively; translational and rotational random errors (σs) were ≤1.6 mm and 0.6º, respectively. Regarding the intrafraction accuracy translational and rotational Σs were ≤0.4 mm and 0.4º, respectively; translational and rotational σs were ≤ 0.5 mm and 0.3º, respectively. Concerning the time-intrafraction displacements correlation Pearson coefficient was 0.5 for treatment fractions with time between position checks less than or equal to median value, and 0.2 for those with time between position controls longer than the median figure. These results suggest that intrafractional patient motion is smaller than interfractional patient motion. Moreover, we can state that application of different imaging verification protocols translate into a relevant difference of accuracy for the same immobilization device. The magnitude of intrafraction displacements correlates with the time for short treatment sessions or during the early phase of long treatment delivery.
Gesehen am 17.05.2021